Factors affecting feed efficiency, feed intake and daily gain of Awassi lambs - AZIZ, D A; ALKASS, J E; AL-NIDAWI, KA (The Indian Journal of Animal Sciences, 2013)
Daily gain, feed efficiency and feed intake of Awassi lambs during the 0·40 and 41-80 days post- weaning periods were studied. The overall means for daily gain, feed efficiency and feed intake were 160±7.7 and 145±7.0 g/day. 5.480±0.2 and 8.83±0.39 kg feed intake/kg live weight gain. and 827±24 and 1053±28 g/day during periood (0-40) and period 2 (41·80) respeclively. Daily gain was affected only by the larning season (1<0.01) in both the periods, and by the dam weight (1<0.01) during period 1. Feed efficiency was affected significantly (P<0.01) by lambing season during periods 1 (P<0.05) and during period 2. and by lype of birth (1<0.01) during period 1. Heritability estimates of fecd efficiency. feed intake and daily gain during periods 1 and 2 were 0.33±0.1 and 0,28+-0.09, 0.39±0.07 and 0.32±0.10, and 0.33±0.09 and 0.25±0.09 respectively. Genetie and phenotypic correlations between feed efficiency and daily gain ranged from .0.39 to .0.45, and those between feed intake and daily gain from 0.32 10 0.40 in both the periods. Expected genetic progress in feed efficiency. feed intake and daily gain through individual selection would be 2.3 anu 1.75. 2.12 and 1.64. and 2.89% and 2.5% during periods 1 and 2 respectively